Evolutionarily conserved BON1 regulates the basal cytosolic Ca 2+ level by calmodulin-independent activation of Ca 2+ pumps in Arabidopsis - Zhan Li; Hyo Jung Kim; Laura Luoni; Carolina Conter; Nicola Masè; Francesca Resentini; Peiqiao Xie; Alessandra Astegno; Maria Cristina Bonza; Jian Hua (Proceedings of the National Academy of Sciences, 2025)
Plasma membrane-localized autoinhibited Ca 2+ pumps are essential for maintaining basal cytosolic Ca 2+ levels for regulating growth processes and environmental responses. These pumps are known to be activated by calmodulins to maintain Ca 2+ homeostasis in plants and animals. Here, we demonstrate that the evolutionarily conserved copine protein BON1 is critical for maintaining low cytosolic Ca 2+ concentrations by directly regulating two plasma membrane-localized Ca 2+ pumps ACA8 and ACA10 in Arabidopsis . BON1 interacts with a region within the N-terminal domain of ACA8 and ACA10, preceding the calmodulin binding sites, and stimulates ACA8 activity. This activation can occur without calmodulin binding, indicating that BON1 and calmodulin independently regulate the Ca 2+ pump. Loss of BON1 function results in elevated basal cytosolic Ca 2+ concentrations, which can be partially rescued by overexpressing hyperactive ACA8 or ACA10. Furthermore, we show that BON1 has one high-affinity Ca 2+ binding site in the VWA domain that is critical for activation of ACA8 as well as for BON1 function, suggesting a feedback mechanism for Ca 2+ homeostasis at resting concentrations. Our findings suggest that this Ca 2+ responsive regulatory mechanism extends beyond Arabidopsis , as we show interactions between ACA and BON proteins from algae to flowering plants, pointing to an ancient regulatory mechanism for maintaining low basal cytosolic Ca 2+ . Notably, a human plasma membrane-localized autoinhibited Ca 2+ pump can also be activated by a human BON protein in a yeast functional assay system, suggesting evolutionary conservation in Ca 2+ regulation across species.